Transformational and Instructional Leadership in Cross-Thematic Teaching - Gaitanidou, Athanasia; Laios, Athanasios; Derri, Vassiliki; Chatzoudes, Dimitrios (International Journal of Education Policy and Leadership, 2023)
Over the last decades, rigorous research has been carried out concerning the most appropriate leadership style of school principals and the two basic conceptual models of transformational and instructional leadership. However, the practices and behaviours of principals as they affect the successful implementation of cross-thematic integration have not been sufficiently explored. This article examines the relationship between the factors’ “transformational leadership” and “instructional leadership” for enhancing cross-thematic teaching. Quantitative empirical research was conducted on a sample of 251 principals of Greek primary schools. The results reveal a positive and statistically significant relationship between the two main factors of this study.